2012
DOI: 10.1111/j.1744-7941.2011.00004.x
|View full text |Cite
|
Sign up to set email alerts
|

Abusive supervision and workplace deviance: the mediating role of interactional justice and the moderating role of power distance

Abstract: This study replicates previous studies by examining the effects of abusive supervision on employee deviant behaviours in the Chinese organisational context. It extends the existing research of abusive supervision by investigating the mediating role of the perception of interactional justice and the moderating role of individual‐level power distance in the link between abusive supervision and workplace deviance. Regression analyses on data of 283 employee–supervisor dyads revealed that the perception of interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
118
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(135 citation statements)
references
References 55 publications
(99 reference statements)
14
118
1
2
Order By: Relevance
“…Similarly, Lin, Wang, and Chen (2013) reported that subordinates in high power distance culture respond less negatively to supervisory abuse. In a similar vein, Wang, Mao, Wu, and Liu (2012) reported less interactional injustice of abused employees in a high power distance culture.…”
Section: Impact Of National Culture On Subordinate's Perception Of Abmentioning
confidence: 78%
See 1 more Smart Citation
“…Similarly, Lin, Wang, and Chen (2013) reported that subordinates in high power distance culture respond less negatively to supervisory abuse. In a similar vein, Wang, Mao, Wu, and Liu (2012) reported less interactional injustice of abused employees in a high power distance culture.…”
Section: Impact Of National Culture On Subordinate's Perception Of Abmentioning
confidence: 78%
“…As these both countries are totally different from each other on the basis of their economic situation, religion and especially on their cultural grounds. Aryee, Chen, Sun, & Debrah, 2007;Jian et al, 2011;Wang et al, 2012;Wei & Si, 2013;Xiaqi, Kun, Chongsen, & Sufang, 2012;Xu, Huang, Lam, & Miao, 2012) 2 North America (Tepper, 2000;Tepper 2007;Tepper et al, 2009;Tepper et al, 2006;Tepper, Duffy, Hoobler, & Ensley, 2004;Tepper, Duffy, et al, 2001;Tepper et al, 2008;Tepper, Lockhart, & Hoobler, 2001;Tepper et al, 2011;Tepper et al, 2007;Ashforth, 1994Ashforth, , 1997Bowling & Michel, 2011;Carpenter, Geletkanycz, & Sanders, 2004;Christmas, 2007;DelBel, 2003;Dupré, Inness, Connelly, Barling, & Hoption, 2006;Namie & Namie, 2009;Tsapatsis, 2012) 3 Australia (Grice et al, 2003 ;Ng, 2010 ;Kiazad et al, 2010) 4 United Kingdom (Turnbull, 1995;Deborah, 2000;McMillan, 1995) 5 Pakistan , Khan, 2010Khan, 2014aKhan, , 2014bKhan, , 2014cImran, 2010;Mukhtar et al, 2010;Bashir & Hanif, 2011;Gadit & Mugford, 2008) 6 Israel (Dana Yagil, 2006) 7 Turkey …”
Section: Selection Of Hofstede's Cultural Dimensions For Present Studymentioning
confidence: 99%
“…This research has also supported the conceptualization of workplace aggression as a job demand in the COR theory and the JDR model, as workplace aggression depletes an individual's mental resources through taxing their self-regulatory strength (Wang, Mao, Wu & Liu, 2012). Research specific to how abusive supervision impacts an employee's enjoyment towards their work tasks is limited.…”
Section: The Terminological Diversity Problemmentioning
confidence: 95%
“…Second, workplace aggression research has shown that as the levels of power distance between the perpetrator and victim grows the impact of workplace aggression also increases (e.g., Tepper et al, 2009;Thau et al, 2009;Wang, Mao, Wu & Liu, 2012). This occurs as workplace aggression and the power distance impact the victim's sense of justice (both distributive and interactional; Thau & Mitchell, 2010;Wang, Mao, Wu & Liu, 2012).…”
Section: The Terminological Diversity Problemmentioning
confidence: 99%
See 1 more Smart Citation